2017
DOI: 10.1039/c7nr04138a
|View full text |Cite
|
Sign up to set email alerts
|

Single-trigger dual-responsive nanoparticles for controllable and sequential prodrug activation

Abstract: Here we have developed a novel approach where two synergistically acting drugs were completely inactivated upon chemical immobilization on a nanoparticle template and activated in response to a chemical stimulus. The activation rate of each drug payload is controlled using a biologically inert bioorthogonal chemistry approach. By exploiting the subtle differences in the 'click-to-release' bioorthogonal reaction, we engineered a single delivery platform capable of releasing the payloads in a time-staggered mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Structural elements of TCO were explored to introduce additional hydrophilic groups, as illustrated in Scheme 1. At the core of the protodrug structures is a heterobifunctional TCO [36][37] bearing a carboxylic acid at a tertiary carbon, which was regioselectively modified with cytotoxic compounds on one end and functionalized with hydrophilic groups, such as glycine or aspartic acid on the other. Importantly, the TCO carboxylate used is 99% enantiomeric excess (ee) at that tertiary chiral carbon, so that only single diastereomers of the protodrugs are formed.…”
Section: Protodrug Design Synthesis and In Vitro Evaluationmentioning
confidence: 99%
“…Structural elements of TCO were explored to introduce additional hydrophilic groups, as illustrated in Scheme 1. At the core of the protodrug structures is a heterobifunctional TCO [36][37] bearing a carboxylic acid at a tertiary carbon, which was regioselectively modified with cytotoxic compounds on one end and functionalized with hydrophilic groups, such as glycine or aspartic acid on the other. Importantly, the TCO carboxylate used is 99% enantiomeric excess (ee) at that tertiary chiral carbon, so that only single diastereomers of the protodrugs are formed.…”
Section: Protodrug Design Synthesis and In Vitro Evaluationmentioning
confidence: 99%
“…Dox‐TCO‐NHS is a small molecule prodrug which is synthesized for the assembly of a Dox nanodrug formulation (Scheme and Scheme S1 in the Supporting Information). The attached Dox can be released from nanodrug assembly through bond‐cleaving bioorthogonal chemistry in response to tetrazine . We have previously demonstrated that toxicity of Dox‐TCO (IC 50 =98 nM for Dox‐TCO) increases fivefold after its reaction with tetrazine uncaging unmodified doxorubicin (IC 50 =480 nM for Dox) .…”
Section: Resultsmentioning
confidence: 99%
“…The Dox is first derivatized with NHS‐TCO‐NHS which is necessary for its subsequent attachment to NP surface for click‐to‐release studies. This derivatization offers several useful features; that is, 1) cytotoxicity is decreased with TCO modification, 2) resistance to release in response to endogenous factors and, 3) Dox release specific to its nontoxic chemical partner …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the drug can be administered more selectively under imaging guidance. Several studies have substantiated the crucial role of nanomaterials for diagnosis and imaging based on tetrazine-responsive bioorthogonal cleavage [108][109][110][111]. For example, a vinyl ether-caged camptothecin prodrug and tetrazine-quenched near-infrared fluorophore were separately encapsulated into liposomes, which localized to tumors due to the EPR effect [112].…”
Section: Theranosticsmentioning
confidence: 99%